Korean Immigrants in Native Speaker by Chang-rae Lee and Clay Walls by Ronyoung Kim - Kohlová, Petra (Univerzita Pardubice, 2019)
This master thesis deals with the portrayal of Korean immigrants and Korean Americans in the 20th century as captured in Native Speaker by Chang-rae Lee and Clay Walls Ronyoung Kim. Both novels are analysed mainly in terms of identity, acculturation, discrimination and model minority issues. Generation differences are also analysed. In several aspects, the novels are compared to assess the differences in Korean American lives in various decades and different places of the United States of America, particularly California and New York. The aim of the thesis is to describe the struggles and other influences on the lives of Korean Americans.
Korean Immigrants in Native Speaker by Chang-rae Lee and Clay Walls by Ronyoung Kim
Keywords: Američané korejského původu; imigranti; Chang-rae Lee; Kimová, Ronyoung; Native Speaker; Clay Walls; Korean Americans; immigrants; Chang-rae Lee; Kim, Ronyoung; Native Speaker; Clay Walls